Thinking the ‘Culture Wars’ and the Present Political Crisis with the Young Marx (and Friends) - Ben Whitham (tripleC: Communication, Capitalism & Critique, 2018)
We stand at a key juncture: a Western political crisis arose in 2016-17 to match the deep economic crisis of the preceding decade. Events and new social movements of recent years seem to hail the collapse of the project of liberal democracy, though it is hard to see what will replace it. Among the conceptual and analytic tools bequeathed by Marx are those necessary to better understand and anticipate the direction of this key historical moment – from Donald Trump, Brexit and the so-called ‘culture wars’ to the horizon of liberal democracy itself. In this reflection, I suggest some ways in which Marx’s early thoughts on the liberal state and civil society can and should help us to better understand and explain our present predicament. To say that the Young Marx can help us today with what he called ‘the ruthless critique of everything existing’ is not to say that he can do so alone. It is precisely the issues overlooked or ‘fudged’ by Marx and Marxism – gender, sexuality, and race/racism for example – that now sit at the centre of our ‘culture wars’, alongside but never reducible to the contradictions and crises of capitalism. I conclude that it is only with the help of other writers of the 20th and 21st centuries, from Antonio Gramsci to Frantz Fanon and bell hooks, that we can usefully mobilise the Young Marx today, to critique the world as we find it and especially – the very ‘point’ of theory according to Marx – to change it.